Modeling Cholera Dynamics with Vaccination and Asymptomatic Transmission: A Mathematical Framework for Outbreak Control - Hassan Muhammad; Alagbe S.O. Philip Issa Tsado; Angel Otse Ogbu (Darul Yasin Al Sys, 2026)
Cholera remains a persistent public health challenge in regions with limited access to clean water and adequate sanitation. Although mathematical models have substantially advanced understanding of cholera dynamics, the waning effectiveness of vaccination and the contribution of asymptomatic carriers to disease transmission have received comparatively limited attention. This study develops a mathematical model that incorporates these two epidemiologically important mechanisms to evaluate cholera transmission dynamics and outbreak-control strategies. The model stratifies the population into susceptible individuals (S), vaccinated individuals (V), asymptomatically infected individuals (A), symptomatically infected individuals (I), individuals receiving treatment in health centers (C), recovered individuals (R), and the concentration of bacteria in the aquatic environment (B). The basic reproduction number (R₀) was derived, indicating that cholera can be eliminated when R₀ < 1. Using data from cholera outbreaks reported between 2022 and 2025, numerical simulations were conducted to assess alternative intervention strategies. Sanitation measures alone reduced total cases by 43.1%, vaccination by 37.3%, and treatment by 28.0%, whereas the combined implementation of vaccination and sanitation produced a 69% reduction. Sensitivity analysis identified the human-to-human transmission rate (β₁), environment-to-human transmission rate (β₂), and vaccine effectiveness (σ) as the most influential parameters governing disease control. The findings demonstrate that integrated interventions are substantially more effective than single-control strategies and highlight the importance of combining vaccination campaigns with water, sanitation, and hygiene programs. This model contributes to cholera epidemiology by simultaneously accounting for asymptomatic transmission and waning vaccine effectiveness, thereby providing a quantitative framework for designing more effective outbreak-control policies.